There is a role for surgical resection in patients with oligometastatic pancreatic cancer - Targarona Modena, Javier (2021)
Objective: The objective of this work is to retrospectively analyze the resection in patients with oligometastatic stage IV pancreatic adenocarcinoma, after first-line chemotherapy for metastatic pancreatic cancer, evaluating the survival of these cases. Materials and methods: Between January 2005 and December 2019, 5 patients diagnosed with oligometastatic pancreatic cancer undergoing first-line chemotherapy were retrospectively evaluated, after which resective surgery was performed. Results: The resective surgery performed in these patients were: three distal pancreatectomies with splenectomy, one duodenopancreatectomy and one total pancreatectomy. All received chemotherapy treatment; three patients received treatment with Folfurinox, one received 5-fluorouracil, and one received gemcitabine plus capecitabine. The patients received an average of 4 months of chemotherapy (3-6 months) and after this, resective surgery was scheduled. The average survival in these patients was 23 months (11 to 39 months), only one patient presented recurrence of the disease and died at 28 months, the remaining 4 are alive. Conclusion: Resective surgery in patients with stage IV pancreatic cancer can be done safely. This could be considered in selected patients with a good radiological and biochemical response after an adequate period of chemotherapy in whom there is no obvious distant disease.